The 'Healthy Worker Effect': Do Healthy People Climb the Occupational Ladder? - Joan Costa-i-Font; Martin Ljunge (Center for Economic Studies and ifo Institute (CESifo), 2017)
The association between occupational status and health has been taken to reveal the presence of health inequalities shaped by occupational status. However, that interpretation assumes no influence of health status in explaining occupational standing. This paper documents evidence of non-negligible returns to occupation status on health (which we refer as `healthy worker effect'). We use a unique empirical strategy that addressed reverse causality, namely an instrumental variable strategy using the variation in average health in the migrant's country of origin, a health measure plausibly not determined by the migrant's occupational status. Our findings suggest that health status exerts significant effects on occupational status in several dimensions; having a supervising role, worker autonomy, and worker influence. The effect size of health is larger than that of an upper secondary education.
Keywords: J50; I18; 330; occupational status; self-reported health; immigrants; work autonomy; supervising role